Civil társadalom változás idején: szűkülő, változó, táguló terek és egy új szabályozási szemléletmód szükségessége = Civil society in times of change : shrinking, changing and expanding spaces and the need for new regulatory approaches - Anheier, Helmut K.; Lang, Markus; Toepler, Stefan (Civil Szemle, 2020)
The relationship between many G20 governments and organized civil society has become more complex, laden with tensions, and such that both have to find more optimal modes of engagement. In some instances, state-civil society relations have worsened, leading some experts and activists to speak of a "shrinking space" for civil society. How wide- spread is this phenomenon? Are these more isolated occurrences or indeed part of a more general development? How can countries achieve and maintain an enabling environment for civil society? The authors suggest that much of the current impasse results foremost from outdated and increasingly ill-suited regulatory frameworks that fail to accommodate a much more diverse and expanded set of civil society organizations (CSO). In response, they propose a differentiated model for a regulatory framework based on functional roles Based on quantitative profiling and expert surveys, moreover, the paper also derives initial recommendations on how governments and civil society could find ways to relate to each other in both national and multilateral contexts.
Gesehen am 14.09.2020